A tomada de decis??o para a sele????o de projetos em uma empresa do setor de engenharia el??trica - Oliveira Filho, Nestor de (2015)
In today's business environment, where the participation of Small-Medium Enterprises (SMEs) in local, national and international economies has been increasing, it becomes important to deepen understanding of the strategic decisions made by such organizations, since most studies on the subject deal with large organizations. This dissertation investigates the process, the features and the factors that influence the decision-making for the selection of new projects in a SME in the Brazilian engineering sector. The methodology chosen was the single case study applied in the target company and the results made it possible to verify the performance of a less complex form of decision-making than presents the theoretical models on the subject, which would not necessarily be a problem. However, the process is characterized by problems of lack of periodicity, limited analysis to organizational factors and decisions made with a personalized and emotional charge, as the final decision is executed by the main manager of the organization. As theoretical contribution is the need to develop a literature that highlights best practices for decision-making in SMEs, especially, the Brazilian. As a practical contribution to the managers of those organizations, it indicates the need to deal with more relevance the improvement of stages to the decision-making process and for governments and associations linked to SMEs, there is the need for investment and sponsorship programs aimed to the subject.